Gemma and the ultimate standoff - Zappa, Shana Muldoon (Star Darlings, 2016)
"As the Star Darlings prepare for the Starshine Day celebration, Gemma impatiently waits to be sent on her wish mission in which she hopes to collect enough energy to correct the energy crisis"--OCLC.